2022
DOI: 10.1001/jamainternmed.2021.7556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Ward-Based Program on Hospital-Associated Complications and Length of Stay for Older Inpatients

Abstract: Hospital-associated complications of older people (HAC-OPs) include delirium, hospital-associated disability, incontinence, pressure injuries, and falls. These complications may be preventable by age-friendly principles of care, including early mobility, good nutrition and hydration, and meaningful cognitive engagement; however, implementation is challenging.OBJECTIVES To implement and evaluate a ward-based improvement program ("Eat Walk Engage") to more consistently deliver age-friendly principles of care to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“… 19 While our findings validate results from a previous meta-analysis 3 showing that LOS was reduced for medical patients who were allocated to a discharge planning program, other investigations found no or even an increasing effect on LOS among unselected medical patients. 6 , 34 Interventions in smaller and more selected patient populations, such as in those with heart failure, were more likely to be successful in reducing LOS. 35 To increase reach, however, this study included a broad and heterogeneous population of medically complex patients with multiple acute and chronic morbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 While our findings validate results from a previous meta-analysis 3 showing that LOS was reduced for medical patients who were allocated to a discharge planning program, other investigations found no or even an increasing effect on LOS among unselected medical patients. 6 , 34 Interventions in smaller and more selected patient populations, such as in those with heart failure, were more likely to be successful in reducing LOS. 35 To increase reach, however, this study included a broad and heterogeneous population of medically complex patients with multiple acute and chronic morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…As in other countries, this raised safety concerns. 4 Several approaches have been developed to optimize LOS, some focusing on aspects of patient management, such as clinical care, 5,6 and others targeting staffing models 7,8 and logistics of care coordination (eg, discharge planning and application of interprofessional care). 3,[9][10][11] Nevertheless, hospital discharge planning procedures have not been widely standardized, carrying the risk of poor communication, delayed assessments for postacute care demands, medication errors, or unprepared patient discharges.…”
Section: Introductionmentioning
confidence: 99%
“…It was initially developed and evaluated through pre-post studies on a medical and a vascular surgical ward in a major metropolitan teaching hospital in Brisbane, Australia, which showed improved care processes and team communication, reduced length of stay and increased discharge home (Mudge et al, 2015(Mudge et al, , 2020. The program was then tested in a cluster randomized trial across four hospitals that confirmed the model was scalable and demonstrated a significant reduction in delirium (Mudge et al, 2022). This led to government funding to scale up across 17 metropolitan and regional publicly funded hospitals throughout Queensland since mid-2019.…”
Section: The Eat Walk Engage Programmentioning
confidence: 99%
“…When talking through these options with them, we often cite the risk of adverse events from hospital admission (hospital acquired infections, pressure sores, deconditioning, and so on) as one good reason to stay at home. A cluster randomised controlled trial of a structured, ward based, improvement programme called “Eat Walk Engage” sought to reduce hospital acquired complications among older people 1. No reduction in hospital associated complications was observed between patients on the four wards that received the intervention (aimed at improving nutrition, hydration, mobility, and cognitive and social engagement) and the four control wards.…”
Section: There’s No Place Like Homementioning
confidence: 99%